Menilai pemberlakuan pembuktian terbalik pada tindak pidana pencucian uang sebagai kejahatan proxy di dalam aset Kripto - Patricia Edina Sembiring (Integritas: Jurnal Antikorupsi, 2024)
Perpetrators of money laundering have found a new medium by using crypto assets to launch their actions. Money laundering is a proxy crime as a manifestation of actions aimed to covering up crimes secretly, especially using third parties as intermediaries. Therefore, by using this new complexity mechanism, it will be increasingly difficult for law enforcers to prove money laundering crime. This difficulty occurs due to the anonymity of crypto assets so that the perpetrators can easily carry out their actions. In using normative juridical research methods and a conceptual approach, this research aims to look again at the use of evidentiary mechanisms in dealing with money laundering, mainly when carried out through crypto assets. Based on the research results, the implementation of stand-alone money laundering in Article 69 and reversal burden of proof in Article 77 on the Law of Money Laundering is considered ineffective in ensnaring perpetrators on crypto assets because: (1) they will have difficulties in finding the subjective and objective elements of the perpetrator, (2) the practice of reversal burden of proof evidence is still unclear in Indonesia. Meanwhile, re-enforcing negative evidence based on law can be implemented as a form to handle money laundering perpetrators in crypto-asset transactions.